Manajemen Pendidikan Karakter di SMA Negeri 13 Ambon - Sunardi Djamaluddin; P. Rahabav; A. Sahalessy; Sumarni Rumfot (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
This research aims to (1) To find out the character education planning at SMA Negeri 13 Ambon. (2) To find out the organization of character education at SMA Negeri 13 Ambon. (3) To find out the implementation of character education at SMA Negeri 13 Ambon. (4) To find out the supervision of character education at SMA Negeri 13 Ambon. (5) To find out the factors that support and detain character education at SMA Negeri 13 Ambon. The results of this research are: (1) Educational character management planning at SMA Negeri 13 Ambon begins with a program planning meeting at the beginning of the year involving all school components including the principal, vice principal for curriculum, student affairs, infrastructure, public relations, treasurer, education staff and education and school committees. The meeting discussed determining the goals of character education, preparing programs and integrating character values ​​to students. (2) The organization of character education for students of SMA Negeri 13 Ambon was carried out based on a Decree from the principal to all stakeholders of SMA Negeri 13 Ambon, with regard to what, where and when the activities will be carried out, why it must be implemented, and how to implement it. (3) The implementation of character education at SMA Negeri 13 Ambon was carried out in integrative way by all teachers including the principal. (4) Supervision of character education at SMA Negeri 13 Ambon was carried out by internal and external supervisors. The internal supervisor is the principal, assisted by the vice principal, while the external supervisor is a school supervisor assigned by the Educational Office. The Implementation is carried out in accordance with their responsible and functions, based on the instrument of supervision activities, both monitoring and evaluation. (5) The supporting factor for character education management in SMA Negeri 13 Ambon is, there is a coordination between the principal and the vice principal, teachers and staffs in implementing various models, methods and learning strategies in character education in teaching and learning process, inside and outside the classroom, supported with adequate infrastructure. The only factor detaining the management of character education in SMA Negeri 13 Ambon is the lack of self-awareness of certain subject teachers.